Osztály vagy réteg? Történeti változások, emberi tőke, karrierminták a foglalkozási osztály- és réteghelyzet vizsgálatában - Bukodi, Erzsébet (Szociológiai Szemle, 2024)
The paper focuses on comparing the traditional occupational schema developed by Andorka to the EGP class classification in the Hungarian society. In the empirical analysis, cleavages between manual-non manual labour; employer-self-employed-employee position; managerial/supervisory subordinated position; skilled-unskilled labour, and working for primary-industrial-tertiary sector are considered.Data used for the analysis come from the Social Mobility and Life History Survey of the Hungarian Central Statistical Office and cover the full job history of more than 10,000 male and 10,000 female respondents who entered into the labour force after 1950. Data are converted to a person-period file and event history method is applied for testing historical changes of career mobility recruitment into the various class positions. For this purpose multinominal logistic regression analysis is performed in order to present the cumulative class career mobility patterns. Independent variables of the models, fitted separately for men and women, are historical year, formal level of education, job qualifications, first class position and work experience.Results are interpreted in the light of human capital investment and labour market mobility theories. The paper provides clear evidences for the validity of the EGP schema for Hungary, however, some specific features have to be considered if applying this classification in Hungary.